An Improving Electricity Wiring Safety Based Ecu-Design For Energy Consumption Monitoring Apartments In Medan - Erichand Ricahardo Sagala; Solly Aryza; Hamdani (Sean Institute, 2021)
In this era of information households, electrical energy consumption is divided into two, namely the low economy class which consumes the most electricity, around 20.00%, and the upper-middle economic class which consumes the most electricity. about 20.00 to 32.00% ac. Vertical living is widespread in the middle economy class, with occupancy increasing by 9.52% in 2017. In this situation, an analysis of energy consumption and savings is required. The problem of the simple rental apartment case in Medan Asia Mega Mas Indonesia is a clear example of the need for an energy monitoring system. this is due to the use of electricity that is not by the function of the apartment, such as air conditioning and washing machines. Energy meter systems measure the voltage and current of electrical equipment connected to the system. the voltage sensor used is zmpt101b5 and the current sensor used is acs712. The design of this energy meter system can measure the voltage and current of electrical equipment with an error rate of 4.40%. according to the measurement results, the air conditioning system is the most power-consuming resource in the 800kwh range.